Financial Literacy and Emotional Intelligence as Predictors of Financial Behavior among Undergraduate Students - Adhikari, Madhav; Adhikari, Khem (Journal of Emerging Management Studies, 2026)
Purpose – The main purpose of this study is to examine the effect of financial literacy, financial risk  tolerance,  and emotional  intelligence on  financial  behavior  among  undergraduate  students  of Tribhuvan University.Design/methodology/approach – The research design adopted in this study was a causal. This study collected the relevant data based on a structured questionnaire with the help of five-point Likert scale among 155 students of Tribhuvan University. The data were collected through a convenience sampling method, and were analyzed using SPSS to determine the relationship between variables.Findings – The findings show that emotional intelligence, financial literacy, and financial risk tolerance had a significant influence on financial behavior of undergraduate students.  High  financial  literacy  and  emotional  intelligence were seen as good predictors of better financial  practices.  The  outcomes  of  the research revealed that financial literacy and emotional intelligence can be relevant to the enhancement of financial behavior among students of the university.Implications – The implications of the research address on improving the levels of financial literacy and emotional intelligence which helps students achieve good financial habits. Governments and educational institutions are supposed to incorporate financial education and skills training in the curriculum to enhance the financial decision-making process of students.Originality/value – The research enhances its significance by highlighting how cognitive financial knowledge and emotional competencies jointly influence students’ budgeting, saving, spending, and financial decision-making practices. The findings are expected to provide useful insights for educators, policymakers, and financial institutions in designing educational interventions and financial awareness programs that promote responsible financial behavior among young adults.